Psychological characteristics of Norwegian adolescents reporting no likelihood of visiting a dentist in a situation with toothache - ERIK SKARET, EINAR BERG, GERD KVALE, & MAGNE RAADAL (IAPD and Blackwell, 2007)
The dental personnel regularly have to deal with patients showing behavioural management problems and avoidance behaviour, varying from irregular dental attendance to dropout from dental care.